Application of Lipidomics in the Researches of Food Quality - Haolei HAN; Guangqin LIAO; Yuxuan WU; Houru LI; Yongzhong QIAN; Jing QIU (Shipin gongye ke-ji)
Lipidomics, as a metabolomics approach centered on lipids, aims to comprehensively analyze lipids within biological systems. In recent years, mass spectrometry (MS)-based lipidomics analysis techniques have been widely utilized to address qualitative and quantitative challenges of lipids within complex food matrices, leveraging their high sensitivity, high resolution and broad coverage. Firstly, this paper reviewed the workflow of lipidomic analysis, including sample pretreatment, multi-category mass spectrometry data acquisition and analysis. Subsequently, the applications of lipidomics in the researches of food quality were discussed, emphasizing lipidomics contributes to the analysis of food flavor formation mechanisms and the evaluation of food nutritional functions. Finally, the development trend of lipidomics in food quality research were prospected, aiming to provide important references for further exploration and utilization of lipid resources in food.